Natsumi's song of summer - Weston, Robert Paul (Tundra, an imprint of Penguin Random House Canada Young Readers, 2020)
"This sweet and gentle picture book celebrates summer in Japan, as one little girl shares her love for insects with her cousin who is visiting from America."--